A Case of Complex Restenosis of Aortoiliac Stent Mimicking Downward Stent Migration - Kim, Tae-Hoon; Shim, Won-Heum (Soonchunhyang medical science, 2012)
We present the case of aortoiliac stent restenosis which was caused by 13 years’ of neointimal progression within and at the edge of the aortoiliac stent at the iliac bifurcation. A 74 year-old man presented with vertigo. We planned 4-vessel cerebral angiography through the right common femoral artery to evaluate his carotid artery but failed due to the catheter jam against the struts of the previously deployed aortoiliac stent. Retrograde sheath angiography through the right femoral artery indicated that the previously implanted stent seemed to have migrated in a downward direction and be embedded in the internal iliac artery. While comparing with the previous angiograms, we found that the implanted stent did not migrate downwardly but was separated from the external iliac artery by newly formed septum of neointimal hyperplasia. We successfully reopened the stenosis using the contralateral approach after widening the struts of the previously deployed T-stents. KCI Citation Count: 0